Insights into relations in community-led urban interventions in the global South: civil society and co-production in Kampala. (October 2022) - Siame, Gilbert; Watson, Vanessa
For many decades, civil society organisations have been instrumental in driving the development agenda in many parts of the world. In the urban global South, these organisations have championed alternative, transformational and transnational grassroots-led urban development practice. An important dimension of their efforts has involved working with the state to jointly produce urban services and the urban space, an approach termed co-production. While the rapidly growing literature on co-production has applauded the efficacy of the approach, there has been no explicit interrogation of how it is affected by clearly visible divisions within communities and civil society. This paper argues that co-production is implemented within the context of a divided civil society and that success depends to a large extent on how these civil society actors address their internal conflicts to engage with the state as a consolidated community force, able to negotiate while resisting capture by a manipulative state.